Cooperative Impact of Curcuma longa and Phyllanthus niruri Extracts on Cytotoxicity in HCT-116 Cells - Ibrahim, Sugeng; Hidayah, Nurul; Rifai, Fauziah Novita Putri; Ginanto, Dede (Stem Cell and Cancer Research (SCCR), 2023)
Background: The combination of herbal extracts has the potential to enhance cytotoxic effects against cancer cells. This study explores the combined cytotoxic effects of Curcuma longa and Phyllanthus niruri extracts on HCT-116 colorectal cancer cells. Objective: To assess the cytotoxic effects of Curcuma longa and Phyllanthus niruri extracts when used in combination and to determine the most effective ratio for inhibiting HCT-116 cell growth. Methods: HCT-116 cells were treated for 24 hours with varying concentrations of Curcuma longa and Phyllanthus niruri extracts based on the IC50 values of each extract administered individually. The concentrations for Phyllanthus niruri were 164 µg/mL (one part), 82 µg/mL (half part), and 41 µg/mL (quarter part), while for Curcuma longa the concentrations were 47 µg/mL (one part), 24 µg/mL (half part), and 12 µg/mL (quarter part). Cytotoxicity was assessed using the MTT assay. Results: The combination of Phyllanthus niruri and Curcuma longa extracts demonstrated varied cytotoxic effects. The most effective combination was identified as Phyllanthus niruri to Curcuma longa ratio of 1:0.25, resulting in a 13.5% cell viability rate. Interaction studies using the Chou-Talalay method indicated that the combination index (CI) revealed the most synergistic effect at a ratio of 0.25:0.50. Conclusion: The study identifies that the combination of Phyllanthus niruri and Curcuma longa extracts exhibits synergistic cytotoxic effects on HCT-116 cells, with the optimal combination showing significant inhibition of cell growth. These findings support further investigation into the synergistic potential of these extracts for colorectal cancer therapy.